Radiological Manifestations of Pulmonary Tuberculosis in Palembang, Indonesia: A Retrospective Chest X-ray Analysis - Agustina, Dessy (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Pulmonary tuberculosis (PTB) remains a significant global health concern, particularly in developing countries. Chest X-rays (CXRs) are crucial for initial diagnosis and disease monitoring. This study aims to analyze the radiological manifestations of PTB in patients from Palembang, Indonesia, using a retrospective CXR review. Methods: A retrospective review of CXRs from patients diagnosed with PTB at a tertiary care hospital in Palembang between 2018 and 2022 was conducted. Radiological findings were categorized based on standardized criteria and correlated with clinical and demographic data. Results: A total of 350 patients with PTB were included. The most common CXR findings were: consolidation (65%), cavitary lesions (40%), and hilar lymphadenopathy (30%). A significant association was observed between the extent of radiological involvement and disease severity (p<0.001). Conclusion: This study provides insights into the radiological spectrum of PTB in Palembang. CXRs play a vital role in the early detection and management of PTB. Further research is needed to explore the impact of radiological findings on patient outcomes.